تفسير "قبس من القرآن" للبرقعي : دراسة تحليلية لعقيدة الشيعة الإمامية - عبد الرشيد، محمد أنور (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This paper is an analytical study of a Qur'anic exegesis titled “Tabshi Az Qur'an” by Sheikh Abu al-Faḍl al-Burqaʼi. The research seeks to identify his methods for reforming Twelver shi'ism doctrines such as the Imamate, Wilayah (the state), and infallibility (al-ʼIṣmah) in the light of religious texts. In this regard, the research sheds light on the political and social life of Sheikh al-Burqaʼi, after which we trace the evolution of this thought culminating in his conversion from Twelver shi'ism to the sunnism. We also present an overview of his reform efforts and the ordeals he suffered in pursuit of those reforms. In terms of methodology, we extrapolate from his exegesis of the Qur'an important theological issues pertaining to Twelver beliefs. We then analyse the reforms Sheikh al-Burqaʼi pursued regarding those beliefs and his objective method of analysis and interpretation. The research focuses on the three fundamental beliefs of Twelver shi'ism: Imamate, the state, and the infallibility of their imams and the evidences they cite in support of their beliefs along with the ways they have been interpreted. We then compare those beliefs and interpretations with the thought and analysis of Sheikh al-Burqaʼi as found in his exegesis, and how his ideas agree with the Sunni perspective. The paper concludes that Sheikh al-Burqaʼi was a reformer who refuted with sound evidence, the sectarian myths of Twelver shi'ism, and that his exegesis “Tabshi Az Qur'an” interprets the verses of the Qur'an based on sound Islamic traditions far removed from the novel superstitious of the Twelver interpretation, and that the Qur'anic evidence purported by the Twelver to prove their beliefs violates the correct methods of transmission and contradict sound reason.